Genetic analysis of wheat sensitivity to the ToxB fungal effector from Pyrenophora tritici-repentis, the causal agent of tan spot - Corsi, B.; Percival-Alwyn, L.; Downie, R.C.; Venturini, L.; Iagallo, Elyce; Campos Mantello, C.; McCormick-Barnes, C.; See, Pao Theen; Oliver, Richard; Moffat, Caroline; Cockram, J. (SPRINGER, 2020)
Key message: Genetic mapping of sensitivity to the Pyrenophora tritici-repentis effector ToxB allowed development of a diagnostic genetic marker, and investigation of wheat pedigrees allowed transmission of sensitive alleles to be tracked. Abstract: Tan spot, caused by the necrotrophic fungal pathogen Pyrenophora tritici-repentis, is a major disease of wheat (Triticum aestivum). Secretion of the P. tritici-repentis effector ToxB is thought to play a part in mediating infection, causing chlorosis of plant tissue. Here, genetic analysis using an association mapping panel (n = 480) and a multiparent advanced generation intercross (MAGIC) population (n founders = 8, n progeny = 643) genotyped with a 90,000 feature single nucleotide polymorphism (SNP) array found ToxB sensitivity to be highly heritable (h2 ≥ 0.9), controlled predominantly by the Tsc2 locus on chromosome 2B. Genetic mapping of Tsc2 delineated a 1921-kb interval containing 104 genes in the reference genome of ToxB-insensitive variety ‘Chinese Spring’. This allowed development of a co-dominant genetic marker for Tsc2 allelic state, diagnostic for ToxB sensitivity in the association mapping panel. Phenotypic and genotypic analysis in a panel of wheat varieties post-dated the association mapping panel further supported the diagnostic nature of the marker. Combining ToxB phenotype and genotypic data with wheat pedigree datasets allowed historic sources of ToxB sensitivity to be tracked, finding the variety ‘Maris Dove’ to likely be the historic source of sensitive Tsc2 alleles in the wheat germplasm surveyed. Exploration of the Tsc2 region gene space in the ToxB-sensitive line ‘Synthetic W7984’ identified candidate genes for future investigation. Additionally, a minor ToxB sensitivity QTL was identified on chromosome 2A. The resources presented here will be of immediate use for marker-assisted selection for ToxB insensitivity and the development of germplasm with additional genetic recombination within the Tsc2 region.